Laparoscopic dismembered pyeloplasty in a child with a relatively inaccessible intrarenal pelvis - Hannu Lintula; Hannu Kokki (Wolters Kluwer Medknow Publications, 2011)
Laparoscopic pyeloplasty is an accepted way of dealing with pelviureteric junction obstruction in children with extrarenal pelvis. However, intrarenal pelvis has been considered a relative contraindication for laparoscopic pyeloplasty. Here, we describe the technique of laparoscopic dismembered pyeloplasty in a child with intrarenal pelvis. The key when one embraces laparoscopic dismembered pyeloplasty is to ensure that outcomes are not compromised. A successful outcome requires a widely patent, well-vascularised anastomosis performed free of tension.